2002
DOI: 10.1097/00000372-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Tumorigenic Malignant Melanomas to Dermal Elastin

Abstract: Malignant melanomas, which produce a large number of substances active in connective tissue modulation, must contend with the dermis to grow and propagate. We studied the morphologic interactions between tumorigenic malignant melanomas and dermal elastin. Formalin-fixed and paraffin-embedded tissues of 108 tumorigenic malignant melanomas were stained for elastic tissue with the Verhoeff-van Gieson method. Various aspects of the relationship between malignant melanoma and dermal elastin were analyzed in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous in vitro studies suggesting that the stromal reaction induced by EDPs could promote collagen degradation through collagenase production (Brassart et al , 2001) supports this view. This could explain the histopathological data underlining a strong correlation between elastin fragmentation and melanoma aggressiveness (Breslow, 1970; Feinmesser et al , 2002). Moreover, it was proposed that EDPs could act as factors promoting the transition between melanoma radial growth phase to vertical growth phase in which melanoma cells infiltrate and invade the dermis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous in vitro studies suggesting that the stromal reaction induced by EDPs could promote collagen degradation through collagenase production (Brassart et al , 2001) supports this view. This could explain the histopathological data underlining a strong correlation between elastin fragmentation and melanoma aggressiveness (Breslow, 1970; Feinmesser et al , 2002). Moreover, it was proposed that EDPs could act as factors promoting the transition between melanoma radial growth phase to vertical growth phase in which melanoma cells infiltrate and invade the dermis.…”
Section: Discussionmentioning
confidence: 86%
“…It was suggested that partial preservation of elastic fibres in the tumour depth was a relatively good predictive factor, whereas complete absence of elastin was an adverse one (Feinmesser et al , 2002). However, this study was based on histological analyses and no in vivo studies were carried out to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%